Socioeconomic and Environmental Impacts of Charcoal Production Activities of Rural Households in Mecha District, Ethiopia - Kassahun Tassie; Berihun Misganaw; Solomon Addisu; Ermias Tesfaye (Advances in Agriculture)
Ethiopia is one of the largest charcoal-producing countries in Africa where its urban consumers burn over 3 million tons per year. The purpose of this study was to measure the amount of charcoal produced and its related environmental and socioeconomic impact in the study area. A total of 305 respondents were selected by using a simple random sampling technique. The amount of greenhouse gas emissions from charcoal production was analyzed based on the Intergovernmental Panel on climate change quantification techniques, and the impact of charcoal production on households’ income was analyzed using propensity score matching. The results revealed that the annual charcoal production rate and emission of carbon dioxide equivalent have an increasing trend at an alarming rate in the study area. From propensity score matching analysis, the economic impact of charcoal production has a positive difference of 0.43813162 as compared to nonproducers. Socioeconomic factors like land size, eucalyptus coverage, agricultural extension, market distance, and the number of oxen have a highly significant effect but variables like sex, family size, education status, credit services, and marital status had no significant effect on charcoal production. In general, even though charcoal production is economically having a positive impact on households’ annual aggregate income; it has disproportionality adverse effect on the environment like air pollution in addition to sophisticated respiratory health problems. Therefore, responsible institutions and planners should have focused on the multidimensional effect of traditional charcoal production on environmental issues and sophisticated health problems especially on employed laborers and nearby residents.